The Relationship Between Prenatal Attachment and Compliance with Iron Tablet Consumption in Pregnant Women in the Working Area of the Benteng - Arnianti Arnianti; Kiki Reski Rahmadani Bakri (Jurnal Kebidanan, 2026)
Introduction: Prenatal attachment is a close, warm, and loving cognitive and emotional bond that forms between a mother and her fetus, aimed at the well-being of both the mother and the fetus. This bond is known to encourage healthy behaviors, such as adherence to iron tablet intake during pregnancy. Objective: To determine the relationship between prenatal attachment and adherence to iron tablet consumption in the service area of the Benteng Community Health Center in Palopo City. Methods: A cross-sectional design involving 33 third-trimester pregnant women using total sampling. Prenatal attachment was measured using the Indonesian version of the Prenatal Attachment Inventory (IPAI), and adherence was measured using a questionnaire.  Data analysis was performed using Fisher’s Exact Test. Results: Prenatal attachment was significantly associated with iron tablet adherence (p = 0.004 < p = 0.05). A total of 51.5% of pregnant women had high prenatal attachment, and 60.6% of pregnant women had high adherence. Conclusion: Prenatal attachment, a healthy lifestyle behavior among pregnant women, has been proven effective in improving adherence to iron tablet consumption. A close, warm, and loving emotional bond between the mother and the fetus can be utilized in antenatal care practice.